Attribution of the Record‐Breaking Extreme Cold Event Over Northern East Asia in December 2023 - Hainan Gong; Kangjie Ma; Lin Wang; Wen Chen (Geophysical Research Letters, 2024)
Abstract Against the backdrop of global warming, Northern East Asia experienced a record‐breaking extreme cold event during December 13 to 19 in 2023. The mechanisms behind this extreme cold event remain unclear. This study uses the circulation projection method to detect and quantify the contributions of various factors to this extreme cold event. The findings indicate that large‐scale atmospheric circulation anomalies are the predominant factors triggering this cold wave. The Polar‐Eurasian (POL)‐like teleconnection pattern is identified as a key driver for the cold anomalies, contributing approximately 85% of total cold anomalies in Northern East Asia in this event. Although the POL‐like teleconnection is largely internally generated, the preceding low sea ice levels in the Barents and Kara Seas can strengthen and maintain POL teleconnection. Additionally, preceding November increased snow cover in Northern East Asia can further amplify this cold event by enhancing local surface albedo and reducing incoming solar shortwave radiation.